PJMHS 2022
DOI: 10.53350/pjmhs2216971
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of Silver Diamine Fluoride (SDF) by dentists in Lahore: A cross-sectional study

Abstract: Background: Silver Diamine Fluoride (SDF) has emerged as a promising alternative to the traditional caries management concept of ‘drill and fill’. It offers a conservative, inexpensive, painless and simple way to stop caries progression. Aim: To assess the knowledge and use of Silver Diamine Fluoride among dental practitioners in Lahore. Methodology: A cross-sectional study was conducted after getting institutional ethical approval. A pre-validated questionnaire was used to collect data from 186 dental practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Despite these benefits, SDF is not commonly used or discussed in Pakistan. A recent study conducted in Lahore found that only 25% of dental practitioners surveyed were aware of SDF, but only 10% had used it 6 . It is a concerning finding, particularly given Pakistan's high prevalence of dental caries.…”
mentioning
confidence: 99%
“…Despite these benefits, SDF is not commonly used or discussed in Pakistan. A recent study conducted in Lahore found that only 25% of dental practitioners surveyed were aware of SDF, but only 10% had used it 6 . It is a concerning finding, particularly given Pakistan's high prevalence of dental caries.…”
mentioning
confidence: 99%